Implikasi Pelaksanaan UU N0.32 Tahun 2004 tentang Pemerintah Daerah di Propinsi Jambi (kasus Pilkada langsung dalam hubungannya dengan Otonomi Daerah) - M. Muslih (Jurnal Ilmiah Universitas Batanghari Jambi, 2009)
The general election for the local leaders (popularly known as PILKADA). Very often result in proplems. One of the problems is the damage of the government’s properties caused by the rally of people who are not satisfied with the result of the election. Another problem is the disintegration of the nation. This is because people, during the election, are split into groups of supporters of the candidates running for the elections. These problems are believed to result from the appointment of SKPD that is not based on capability but propinquity. Hence, SKPD fail to show professionalism in their job. As a matter of fact, the on going PILKADA employ two kinds of systems simultenously. The first is union system and the second is federal system. It is suggested that new regulation be issued to enable the discrapancies between the two systems be eliminated so that the two systems can work hand in hand.